(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This work aims to present four concepts of ethics used in the research project “Ethical-non-moralist advertising.” Each concept treats the term differently: ethics as a synonym for morals, ethics as legislation, statute, or code, ethics as a reflection of morals, and ethics as aesthetics of existence. To achieve the objective, this work uses the bibliographic research method and is based on texts produced mainly by the authors Yves de La Taille (2007), Adolfo Sánchez Vázquez (2017), Clóvis de Barros Filho (2014), Bruno Abílio Galvão (2014) and Michel Foucault (2019). With this, understand that the term ethics can have different meanings and understandings, depending on the context in which it is applied.